Environmental Education in The Omah Sawah Community Through The Photovoice Method - Deby Luriawati Naryatmojo; Kusumantoro Kusumantoro; Maharani Intan Andalas (Jurnal Abdimas, 2024)
The Omah Sawah community focuses on environment-based education for children aged 7-13 years. One of the activities is a weekly school held at the Omah Sawah Pavilion every weekend. Activities include environmental observation, flora-fauna identification, yoga, natural batik dyeing introduction, and writing. The limited skills of facilitators, consisting of teenage alumni of Omah Sawah, in innovating learning, and the lack of supporting facilities at Omah Sawah pose challenges. One alternative to enhance learning innovation and instructor skills is by introducing and studying Photovoice. This community service began with preparation, including permission requests and field surveys, followed by curriculum development training using the Photovoice method through lectures and practice. Evaluation was carried out through pre-test and post-test methods. The results showed an increase in participants' knowledge of the Photovoice method and its use in environmental education.